2016
DOI: 10.1073/pnas.1609553113
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Varma: Elucidation of the signal origin for label-free, free-solution interactions

Abstract: In response to the letter submitted by Varma (1), we respectfully disagree with the assertion that our proposed free-solution response function (FreeSRF) model (2) does not explain the signal origin for free-solution measurements. His theoretical considerations are appreciated; however, as we have shown (2), they do not apply here.i) Our empirical model is informative, experimentally consistent, and a reasonable starting point for further elucidating interferometric free-solution, label-free assays. Our approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This RII deviation, expressed with a correction factor x of the aptamer RII, could be triggered by the conformation transition of the aptamer upon recognition to the l -Tym. Such RII deviations were also reported from backscattering interferometry measurement, for recognition systems undergoing significant conformation or hydration changes . As demonstrated by QCM-D and QCM-D-SE experiments, upon l -Tym recognition, the aptamer sensing layer undergoes both a reduction of its thickness and decrease of its hydration ratio. , …”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…This RII deviation, expressed with a correction factor x of the aptamer RII, could be triggered by the conformation transition of the aptamer upon recognition to the l -Tym. Such RII deviations were also reported from backscattering interferometry measurement, for recognition systems undergoing significant conformation or hydration changes . As demonstrated by QCM-D and QCM-D-SE experiments, upon l -Tym recognition, the aptamer sensing layer undergoes both a reduction of its thickness and decrease of its hydration ratio. , …”
Section: Resultssupporting
confidence: 53%
“…In addition to the reduction of the sensing layer thickness, the model highlighted the nonadditivity of refractive index increment (RII) for this recognition system: the RII value of the recognition complex is not equal to the sum of the RII values of the two initial partners . This nonadditivity of the RII for the complex was already measured by Bornhop et al in solution but never revealed on the surface. The recognition was also monitored using a quartz crystal microbalance with energy dissipation (QCM-D), and similar affinity constants were measured around 100 μM for both techniques.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Studies have shown that BSI can detect low concentrations of both ions and saccharides in capillary electrophoresis [12,13,14] and an early study even used a polariometric-BSI configuration to detect an enzymatic reaction with hydroxybutyrate dehydrogenase [15]. There have also been multiple studies on the molecular interactions between protein-sized molecules using BSI [16], but the effect of such interactions on the bulk refractive index and origin of the observed signal has been debated [12,17,18,19].…”
Section: Introductionmentioning
confidence: 99%